2022
DOI: 10.3390/universe8020136
|View full text |Cite
|
Sign up to set email alerts
|

Black Hole Surface Gravity in Doubly Special Relativity Geometries

Abstract: In a quantum gravity theory, spacetime at mesoscopic scales can acquire a novel structure very different from the classical concept of general relativity. A way to effectively characterize the quantum nature of spacetime is through a momentum dependent space-time metric. There is a vast literature showing that this geometry is related to relativistic deformed kinematics, which is precisely a way to capture residual effects of a quantum gravity theory. In this work, we study the notion of surface gravity in a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 94 publications
(153 reference statements)
1
6
0
Order By: Relevance
“…As we saw in [40], the surface gravity obtained from the inaffinity of null geodesics is the same of the one of GR for a generic metric of the form of (17), i.e., independently of the choice of f 1 and f 2 . Here we show that, for any choice of these functions, the surface gravity is a constant, as in GR, when considering massless particles.…”
Section: Zero Lawmentioning
confidence: 69%
See 4 more Smart Citations
“…As we saw in [40], the surface gravity obtained from the inaffinity of null geodesics is the same of the one of GR for a generic metric of the form of (17), i.e., independently of the choice of f 1 and f 2 . Here we show that, for any choice of these functions, the surface gravity is a constant, as in GR, when considering massless particles.…”
Section: Zero Lawmentioning
confidence: 69%
“…In [40] it was found that only for the basis leading to Eq. ( 18) the diverse possible notions of surface gravity coincide.…”
Section: B Deformed Relativistic Kinematics In Curves Spacetimesmentioning
confidence: 99%
See 3 more Smart Citations